(untitled) (Clinics, 2013)
OBJECTIVE: The goal of this study was to observe spontaneous cortical activity and cortical activity modulated by tinnitus-matched sound in tinnitus patients and healthy subjects with no otoneurologic symptoms. METHOD: Data were prospectively collected from 50 tinnitus patients and 25 healthy subjects. Cortical activity was recorded in all subjects with eyes closed and open and during photostimulation, hyperventilation and acoustic stimulation using 19-channel quantitative electroencephalography. The sound applied in the tinnitus patients was individually matched with the ability to mask or equal the tinnitus. The maximal and mean amplitude of the delta, theta, alpha and beta waves and the type and amount of the pathologic EEG patterns were noted during each recording. Differences in cortical localization and the influence of sound stimuli on spontaneous cortical activity were evaluated between the groups. RESULTS: The tinnitus group exhibited decreased delta activity and increased alpha and beta activity. Hyperventilation increased the intensity of the differences. The tinnitus patients had more sharp-slow waves and increased slow wave amplitude. Sound stimuli modified the EEG recordings; the delta and beta wave amplitudes were increased, whereas the alpha-1 wave amplitude was decreased. Acoustic stimulation only slightly affected the temporal region. CONCLUSION: Cortical activity in the tinnitus patients clearly differed from that in healthy subjects, i.e., tinnitus is not a “phantom” sign. The changes in cortical activity included decreased delta wave amplitudes, increased alpha-1, beta-1 and beta-h wave amplitudes and pathologic patterns. Cortical activity modifications occurred predominantly in the temporal region. Acoustic stimulation affected spontaneous cortical activity only in tinnitus patients, and although the applied sound was individually matched, the pathologic changes were only slightly improved.